(untitled) (Romano-arabica, 2025)
The present research attempts to explore the learners’ perspectives regarding the linguistic variation of Arabic and its implication in the learning process. In the last few decades, several proposals have been made to introduce colloquial varieties of Arabic to non-native students, with the aim of meeting their needs, that often include communication in informal settings. The present fieldwork has been conducted in Tunis between December 2020 and July 2021 with informants that were studying either Standard Arabic, Tunisian Arabic, or that were learning both varieties in two separate courses. The data collection was carried out with semi-structured one to one interviews. The study shows the importance of individual factors related to the learners in choosing which variety (or varieties) of Arabic to study, as well as their personal experience in studying one or both and using them outside the classroom. Furthermore, the possibility of mixing more than one variety of Arabic was pointed out by the informants as a communication strategy and, at the same time, as a potential issue in the learning process.